Exploring participatory energy budgeting as a policy instrument to foster energy justice. (August 2017) - Capaccioli, Andrea; Poderi, Giacomo; Bettega, Mela; D'Andrea, Vincenzo
Abstract: The ethical and sustainable production and consumption of energy are becoming increasingly important with the ongoing transformation and decentralization of the energy system. For other kinds of goods and commodities ethical consumption have direct implications for, and the participation of, informed citizens. Due to its intangibility, energy lacks the same levels of reflection and intervention by citizens and those aspects are yet to be fully explored in practice. This paper contributes to the understanding of how energy justice might be approached. We reflect on an empirical experience of participatory energy budgeting, a process aimed at determining how to redistribute a share of energy linked to collective virtuous consumption behaviors. We analyze through a qualitative thematic analysis how participants make sense of the participatory energy budgeting process and the emerged dynamics within the local communities and how this process can strive to reconfigure the relationship among civil society, the energy sector and politics, in order to remediate injustices. We highlight how the construction-in-practice of energy justice in a local community might be closely linked to issues such as the form of energy governance that allows for the participation of citizens and the accountability of the process, policies and technological limitations. Highlights: Energy justice can be related with participatory energy budgeting. One experience of participatory energy budgeting is described. Participatory energy budgeting process enables remediation strategies of energy injustices. Critical aspects are: accountability of the process and community involvement.